Achieving highly efficient bipolar near-ultraviolet emitters via regulating the energy levels of the excited states by a co-acceptor system. Issue 14 (22nd March 2023) - Sun, Yuling; Zhong, Daokun; Liu, Siqi; Yue, Ling; Feng, Zhao; Deng, Xuming; Chen, Xi; Yang, Xiaolong; Zhou, Guijiang
Abstract : The excited state energy-levels are modulated by a co-acceptor system to promote a blue-shift of the emission. Abstract : With the 4-(10 H -phenoxazin-10-yl)benzonitrile oxide 5, 5-dioxide (PhCNTzO) unit as a co-acceptor and 9-phenyl-9 H -carbazole (PhCz) and 9, 9-dimethyl-10-phenyl-9, 10-dihydroacridine (PhAd) groups as electron donors, three novel bipolar near-ultraviolet (NUV) emitters (PhCNTzO- m Cz, PhCNTzO-Cz, and PhCNTzO-Ad ) were designed and synthesized. In order to regulate the energy levels of these emitters to achieve NUV emission, 10 H -phenothiazine 5, 5-dioxide (TzO) was introduced between the p -cyanophenyl group and PhCz or PhAd units. It was shown that the sulfonyl unit together with the p -cyanophenyl group could serve as a co-acceptor system to elevate the energy levels of the excited states from these emitters to furnish NUV emission by fulfilling electron transition from the PhCz or PhAd group with a weak electron-donating ability to the p -cyanophenyl unit. The photoluminescence (PL) peak with higher energy in toluene for these PhCNTzO-based emitters was at 381 nm with a very small CIE y only ca. 0.03. Hence, these PhCNTzO-based emitters showed NUV behavior. Importantly, the photoluminescent quantum yields (PLQYs) of these emitters in toluene were more than 82.7%. As an excellent consequence, organic light-emitting diodes (OLEDs) with NUV emission based on these PhCNTzO-based emitters could achieve a forward-viewing maximum external quantum efficiency ( η ext ) of 5.67% and an EL peak with a higher energy at 416 nm with a CIE y of 0.06. These encouraging EL data show the great potential of the PhCNTzO moiety as a co-acceptor in developing highly efficient NUV emitters.